An urban metabolism of Johor Hahru: material flow analysis (MFA) based and carbon footprint assessment - Nordin, Nazatul Hany (2023)
The primary objective in studying Urban Metabolism is to indicate the sustainability of the city in respect to the interaction between input flows (such as food consumption, water consumption and electricity consumption), output flows (such as waste generation, wastewater and greenhouse gas emissions). Excessive amount of waste generation, wastewater effluent and greenhouse gas emission are major threats to the public health and ecological balance. Material flow analysis and Carbon footprint is used in this study as an approach to determine the urban metabolism framework within the Johor Bahru city. The results, which are based on the downscaled data provided by the government and related case studies, show that the Johor Bahru urban metabolism framework's input and output are balanced in the study area. The aforementioned results show that the consumption of energy material in Johor Bahru has increased in the year 2019. However, the outflows of the level of waste generation, wastewater and greenhouse gas emissions have decreased. Low carbon urban planning and other decision-making processes, are viewed as crucial feedback for enhance the material flows sustainability, efficient performance in energy usage and to reduce the dependency on non-renewable sources.